Secondary traumatic stress disorder in police who handle sexual violence cases - Darmawan, Arif Budi; Nuqul, Fathul Lubabin (UIN Maulana Malik Ibrahim Malang, 2023)
Investigation of criminal cases involving officers who have experienced trauma, such as sexual violence against children, has the potential to experience Secondary Traumatic Stress Disorder (STSD). Secondary Traumatic Stress Disorder (STSD) is a stress disorder that can arise from interactions with someone who experienced a traumatic event. Secondary Traumatic Stress Disorder (STSD) can arise due to one of the triggers, namely emotional contagion, where empathy is often involved in handling cases involving women and children. The study examines the forms of emotional contagion, what factors can cause Secondary Traumatic Stress Disorder (STSD), and how to overcome or prevent the onset of Secondary Traumatic Stress Disorder (STSD). The study was conducted on four police officers who were investigators of sexual violence cases against children in the PPA Unit of Malang District Police. The research uses phenomenological qualitative methods with descriptive data results. Data collection was conducted through semi-structured interviews and processed using thematic analysis techniques—data analysis using coding interview results. Data validity using credibility tested, with triangulation techniques of data sources and member checking. This study found that forms of emotional contagion exist in investigators, such as pity, feel sorrow, sadness, crying, and anger. In addition, several symptoms shown by each subject lead to symptoms of Secondary Traumatic Stress Disorder (STSD), namely intrusive, arousal and avoidance symptoms. It was also found that there was a uniqueness in each subject in how to overcome the onset of Secondary Traumatic Stress Disorder (STSD). STSD in the police has the potential to affect the accuracy in investigating the cases they handle, which then affects law enforcement in the community KEY WORDS police officer; sexual violence; secondary traumatic stress disorderr Copyright ©2023. The Authors. Published by Journal of Indonesian Psychological Science (JIPS). This is an open access article under the CC BY NO SA. link: Creative Commons — Attribution-NonCommercial-ShareAlike 4.0 International — CC BY-NC-SA 4.0